Pseudoartrosi e perdite di sostanza periprotesiche: inquadramento nel paziente a rischio - Calori, G.M.; Mazza, E.L.; Mazzola, S.; Romanò, F.; Colombo, A.; Monzani, V.; Colombo, M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC NON-UNIONS AND BONE DEFECTS: ALGORITHM OF TREATMENT IN PATIENTS AT RISK The incidence of periprosthetic fractures of the femur associated with total hip and total knee arthroplasty varies in different studies. Overall rates have been estimated at 2 to 5%. Although infrequent, periprosthetic femoral non-unions create a debilitating condition for the patient. To date, the literature on the surgical management of femoral periprosthetic non-unions is very limited. Preoperative assessment included history, and radiographic examination. All patients were additionally screened for infection with preoperative laboratory studies. Treatment strategies were determined by the fracture characteristics, implant fixation status and bone quality. In this article, we suggested an algorithm of treatment for periprosthetic femoral non-unions according to our clinical experience and the analysis of the scientific literature.